PENDIDIKAN LINGKUNGAN HIDUP MENGENAI PENGELOLAAN DAN PENGOLAHAN SAMPAH: PERSPEKTIF PESERTA DIDIK - Dewi, Laksmi; Kurniawan, Deni; Matsumoto, Toru; Rachman, Indriyani; Mulyadi, Dadi (EDUTECH, 2020)
Public awareness of waste management and processing in Indonesia is still very low. Likewise, with students,  warnings are still needed in keeping the environment clean. Environmental education (EE) in schools has started to be widely applied in many schools. Ideally, student awareness in keeping the environment, especially in managing waste, becomes better wherever they are. This study aims to explore students’ perceptions of waste management and processing as one of the implementations of environmental management. It is hoped that Environmental Education can have an impact on students’ perception in managing their daily environment. It also explores students’ pereptions at elementary, junior high, and senior high school levels about: (1) environmental education in a school; (2) waste management and processing as part of environmental education; and (3) waste management and processing by local government. Data collection was carried out randomly to several students taking part in Car Free Day (CFD) activity involving 42 student respondents. and the data was processed using descriptive statistics. It was found that firstly, respondents agreed with the application of environmental education in schools through local content subjects, and the Adiwiyata program itself was felt necessary to add insight and knowledge about managing the environment. Secondly, students’ perceptions of waste management as part of Environmental Education was already good, as shown by their preference to keep the garbage if they couldn’t find a place to throw them. Third, waste management and processing by the local government statistically showed good responses. One example is that many dust bins are placed in public location by grouping waste according to their type.    Lingkungan alam di sekitar kita dan dunia saat ini sedang mengalami kerusakan. Salah satu penyebabnya adalah rendahnya kesadaran masyarakat dalam menjaga dan mengelola lingkungan hidup ini. Di Sekolah pendidikan lingkungan hidup (PLH) dilaksanakan sebagai salah satu kurikulum muatan local dengan waktu1 jam pelajaran saja. Tentunya bukan seberapa banyak waktu yang dihabiskan untuk mempelajari kesadaran lingkungan hidup, namun yang paling penting adalah bagaimana mengimplementasikannya dalam kehidupan sehari-hari sebagai upaya membantu menjaga lingkungan hidupnya. Penelitian ini bertujuan untuk mengetahui bagaimana persepsi masyarakat tentang implementasi PLH yang diterapkan oleh peserta didik saat di rumah dan di lingkungan sekitarnya. Bukti real mengetahui kesadaran diterapkannya PLH salah satunya terlihat di ruang public, sebagai contohnya saat pelaksanaan Car Free Day (CFD). Tidak sedikit setelah CFD selesai petugas kebersihan harus membersihkan kembali kawasan karena banyaknya sampah yang dibuang masyarakat tidak pada tempatnya. Data diambil kepada 40 orang secara acak terdiri dari anak usia sekolah SD, SMP, dan SMA, serta orang tua.  Simpulan dari penelitian ini adalah kesadaran masyarakat akan menjaga lingkungan cukup baik. Hanya saja belum ada spesifikasi upaya yang dilakukan oleh masyarakat dalam upaya mengurangi, mengolah, dan menggunakan sampah yang ada agar lebih mermanfaat.